COVID-19 Impact on Community-Based Participatory Randomized Controlled Trials—Lessons From the Oral Health Disparities in Children Consortium - Ramos-Gomez, Francisco J.; Martin, Molly A.; Nelson, Suchitra S.; Borrelli, Belinda; Henshaw, Michelle M.; Curtan, Shelley; Lindau, Helen E.; Rueras, Nicolle; Sandoval, Anna S.; Gansky, Stuart A. (Frontiers in Dental Medicine, 2021)
The COVID-19 pandemic has had a major impact on nearly every sector of science and industry worldwide, including a significant disruption to clinical trials and dentistry. From the beginning of the pandemic, dental care was considered high risk for viral transmission due to frequent aerosol-generating procedures. This resulted in special challenges for dental providers, oral health care workers, patients, and oral health researchers. By describing the effect that the COVID-19 pandemic had on four community-based randomized clinical trials in the Oral Health Disparities in Children (OHDC) Consortium, we highlight major challenges so researchers can anticipate impacts from any future disruptions.